2014
DOI: 10.3390/diseases2020168
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Gastric Carcinogenesis in Helicobacter pylori-Infected Rodent Models

Abstract: Since the discovery of Helicobacter pylori (H. pylori), many efforts have been made to establish animal models for the investigation of the pathological features and molecular mechanisms of gastric carcinogenesis. Among the animal models, Mongolian gerbils and mice are particularly useful for the analysis of H. pylori-associated inflammatory reactions and gastric cancer development. Inhibitors of oxidative stress, cyclooxygenase-2 (COX-2) and nuclear factor-κB, exert preventive effects on chronic gastritis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 115 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…However, the reconstitution of TFF1 abolishes H. pylori -induced expression of these proinflammatory cytokines in gastric cancer cells. Several studies have demonstrated that the proinflammatory cytokines TNF α and IL1 β, known to be induced by NFκB 44 , are associated with gastric disease in rodents after H. pylori infection 45, 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reconstitution of TFF1 abolishes H. pylori -induced expression of these proinflammatory cytokines in gastric cancer cells. Several studies have demonstrated that the proinflammatory cytokines TNF α and IL1 β, known to be induced by NFκB 44 , are associated with gastric disease in rodents after H. pylori infection 45, 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the proinflammatory cytokines TNF-a and IL-1b, known to be induced by NF-jB, 45 are associated with gastric disease in rodents after H. pylori infection. 46,47 Long exposure to proinflammatory cytokines and sustained activation of signaling pathways such as NF-jB due to pathogen infection result in chronic inflammation, which promotes malignancy and tumorigenesis. 5,7,8 Accordingly, our data demonstrated that H. pylori infection of Tff1-KO mice led to significant increases in chronic inflammatory scores, the expression of proinflammatory cytokines, and the development of invasive gastric adenocarcinoma in comparison with uninfected Tff1-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an efficient animal model is crucial to understanding the immunological attributes of different immunogen(s) for vaccine development, which existing models fail to satisfy. Considerable efforts have been made to establish a reliable murine (gerbil or mouse) model to serve this purpose, including extensive application of transgenic animals with single or double mutations, but unfortunately, no significant efforts have been made toward the route of administration to induce an infection [13]. The preexisting method relies on the oral administration of multiple doses of inoculums along with antibiotic pretreatment to induce an infection [14].…”
Section: Introductionmentioning
confidence: 99%